Interview as an Act of Seduction: Analysing Problems I Have Met during My Fieldwork on the Camino de Santiago and in Glastonbury - Tiina Sepp (Journal of Ethnology and Folkloristics)
In this article I am going to analyse my experiences of fieldwork and discuss the role of the researcher in the process of data collection. I will approach problems arising during folkloristic fieldwork and the focus will be on researching belief narrative in personal experience stories. A lot has been written about fieldwork and in this article I am going to add my thoughts on topics that have already been discussed in self-critical reflexive style by several scholars: the different roles of the researcher and the problematic interactional relationship between researcher and informant; power relationships in an interview situation; combining emic and etic perspectives in researching; being ambivalent about which reality we really belong to. I am also going to raise some issues that have to date not been discussed much: the effect of the researcher’s gender on the process of fieldwork; stigmatisation of the supernatural; using the researcher’s own memorates to elicit belief statements from his or her informants; dealing with ‘difficult’ informants. Against the background of the above-mentioned topics lies the liminality of the researcher – while in the field we are in a state of liminality that Victor Turner described when talking about pilgrims and neophytes.